الحنين إلى الأهل في شعر صدر الإسلام - يعقوب عبد الكريم; حبيب وهران (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
الحنين إلى الأهل شعور وجداني ارتبط في شعر صدر الإسلام بجملة من الظروف الذاتية والسياسية والإدارية، عمّقت إحساس بعض الشعراء بالاغتراب عن الأهل، وفجرت حنينهم إلى لقاء القوم. وتتقصى هذه الدراسة الأشعار التي أنشدت في الحنين إلى الأهل في صدر الإسلام، وتعالجها في ضوء الأحوال النفسية، والتاريخية، والاجتماعية التي كونت أزمة الاغتراب لدى فئة من الشعراء في طيات أبيات الحنين وقصائده. لقد أثارت هجرة بعض الشباب إلى الأمصار إحساس بعض الشعراء الشيوخ بالضعف والانهزام، ورُوِّعت الأمهات بثكل الأبناء الأسرى في سجون الأعداء، وأحس بعض الشعراء الأسرى بالمسؤولية تجاه الأمهات والأخوات في الوطن، وعبرت بعض الشاعرات الأزواج والأسيرات، عن حاجتهن الملحة إلى رعاية الأهل وحماية الإخوة، وبكى بعض الشعراء موت الإخوة والأبناء بحرقة نفسٍ تتحسر على مضي زمان الوصال، وترثي فعل الزمان في استلاب الأهل. وعمقت الهجرة إلى الأمصار، بفعل النظم الإدارية شرخ الانفصال بين الشاعر والقوم، فراح يندب فقد الكيان القبلي، ويبدي تفجعه على تمزق روابط الدم وأواصر النسب. وكان في الانتماء إلى الجماعة الإسلامية ما يعزز الشعور الديني، ويعمق الروابط الأخوية، فعبر بعض الشعراء عن حزنهم لفقد إخوتهم المسلمين، واختار بعض الشعراء تحقيق ذواتهم ومكاسبهم بعيداً عن الأهل والقوم، لكن الإحساس بالاغتراب كان ينغص عليهم متعة تحقيق الأهداف، ويحرك في نفوسهم الحنين إلى الأهل والقوم. Homesickness is an emotional feeling. It was attached in the poetry of the prime of Islam to a group of political, administrative, personal circumstances that deepened some poets’ sensation of emigration from his people and burst their longing to meet their nation. These studies investigate verses which were chanted for the purpose of homesickness in the prime of Islam treating it in the light of social, historical, psychological states which made up the crisis of emigration for a group of poets in this age trying to bring out the feelings and sensations that were brought about out of loss which the poets portrayed in verses and poems of longing. The emigration of young men to another countries aroused the old poets’ sensation of weakness and defeat, and mothers were frightened of lossing their captured sons in the prison of enemies. Some poets wailed over the death of brothers and sons with their selves burning and moaning for the passage of the time of contact and elegizing the act of time in robbing their people. The emigration to another countries also deepened the gap of separation between the poet and his people, so he went bewailing over the tribal structure showing his groaning over the rupture of blood relationships and kinship. It had been in the belonging to the Islamic community what reinforced the religious feeling and deepened the brotherly relationships. Therefore, some poets expressed their sadness for the loss of their Muslim brothers, and others chose to realize themselves and their gains away from their people, but the sensation of emigration disturbed the pleasure of achieving aims and moved in their noble selves the longing for their people and nation.